Pengaruh Faktor Makroekonomi pada Return Saham Perusahaan Infrastruktur Tercatat dalam Indeks Saham Syariah Indonesia - Kayla Khaeltisya; Dimas Sumitra Danisworo; Alvianita Gunawan Putri; Novitasari Eviyanti (Journal of Applied Islamic Economics and Finance, 2022)
The purpose of this study is to find out the influence of variable inflation, BI interest rates, exchange rates, and money supply on the Return of Shares of Companies listed in the Indonesian Sharia Stock Index. The dependent variables used in this study are the return of shares of 20 companies listed in the Indonesian Sharia Stock Index, while the independent variables are inflation data, BI interest rates, exchange rates, and money supply. The type of data used in this study is secondary time series data sourced from Bank Indonesia, the Central Statistics Agency, and the Indonesia Stock Exchange for the period 2016 to 2020. The study used the Multiple Linear Regression Analysis method with the classical assumption test, and the hypothesis test used the SPSS application to see the influence of independent variables on dependent variables. The results of this study are that inflation, BI interest rates, and money supply do not have a significant effect on stock returns, while variable exchange rates have a negative and significant effect on stock returns, and simultaneously the four variables do not have a significant effect on stock returns.